INFLUENCE OF ZIRCONIUM ON CORROSION RESISTANCE AND MARTENSITIC TRANSFORMATION OF TI50NI49,5FE0,2MO0,3 - Fitri Azalia, Disha
According to the World Health Organization (WHO), Coronary Heart Disease is the number one cause of death globally. One of the most reliable methods of treating coronary heart disease is by using a self-expandable stent. The alloy that is ommonly used and has good biocompatibility is the Nitinol alloy (TiNi/NiTi). Even though this alloy has been widely used as stent material, there are still many aspects that need to be developed. In some cases, the release of Ni 2+ ions are still very common considering the nickel content is quite high in the alloy, which potentially causes allergic reactions in patients. Thus, further research is needed to improve the performance, corrosion resistance, but still maintain the biocompatibility of the alloy. This study will review the effect of adding Zr on the corrosion rate and martensitic transformation behaviour Shape Memory Alloy Ti50 Ni49.5 Fe0.2 Mo0.3 (TN-10).